2018
DOI: 10.1242/dev.166488
|View full text |Cite
|
Sign up to set email alerts
|

Midface and upper airway dysgenesis in FGFR2-craniosynostosis involves multiple tissue-specific and cell cycle effects

Abstract: Midface dysgenesis is a feature of more than 200 genetic conditions in which upper airway anomalies frequently cause respiratory distress, but its etiology is poorly understood. Mouse models of Apert and Crouzon craniosynostosis syndromes exhibit midface dysgenesis similar to the human conditions. They carry activating mutations of , which is expressed in multiple craniofacial tissues during development. Magnetic resonance microscopy of three mouse models of Apert and Crouzon syndromes revealed decreased nasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 87 publications
(118 reference statements)
1
36
0
Order By: Relevance
“…We observed dramatically increased size and cell number in MC of Fgfr2 +/S252W embryos, with increased proliferation of chondrocytes detected as early as E12.5. Previous studies have shown that Fgfr2 +/S252W mutant mice have increased cartilage of the basicranium (posterior to the hypophyseal cartilage) and thickened nasal cartilage owing to increased chondrocyte proliferation (Wang et al, 2005; Holmes et al, 2018). These results suggest a common mechanism of increased proliferation by the FGFR2 S252W mutation in these cranial cartilages, whether derived from cranial neural crest cells or mesoderm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We observed dramatically increased size and cell number in MC of Fgfr2 +/S252W embryos, with increased proliferation of chondrocytes detected as early as E12.5. Previous studies have shown that Fgfr2 +/S252W mutant mice have increased cartilage of the basicranium (posterior to the hypophyseal cartilage) and thickened nasal cartilage owing to increased chondrocyte proliferation (Wang et al, 2005; Holmes et al, 2018). These results suggest a common mechanism of increased proliferation by the FGFR2 S252W mutation in these cranial cartilages, whether derived from cranial neural crest cells or mesoderm.…”
Section: Discussionmentioning
confidence: 99%
“…LCM was performed as previously described in detail (Holmes et al, 2018). The heads of female Fgfr2 +/+ littermates ( n =3) and female Apert Fgfr2 +/S252W ( n =3) embryos at E16.5 were embedded in OCT without fixation and rapidly frozen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18][19][20][21] Various mouse models expressing FGFR pathogenic variants have been developed and demonstrate phenotypes analogous to the human craniosynostosis syndromes, including premature coronal suture closure and midface flattening (retrusion). [22][23][24][25][26][27][28][29][30][31] Pathogenic variants in TWIST1 (twist family basic Helix-Loop-Helix transcription factor 1) gene, another transcription factor associated with craniosynostosis, [32][33][34] directly affect BMP signaling of skull preosteoblasts, leading to variations in cerebral brain angiogenesis. 35 These animal models as well as studies of cellular behavior in human craniosynostosis cell lines provide the means to examine the structural, cellular, and molecular changes that occur during prenatal development.…”
Section: Normal Development Of the Calvarium And Molecular Determinanmentioning
confidence: 99%